Non-cognitive Support for Postgraduate Studies: A Systematic Review - Frantz, Jose; Cupido-Masters, Jill; Moosajee, Faranha; Smith, Mario R. (Frontiers in Psychology, 2022)
Retention of postgraduate students is a complex problem at higher education institutions. To address this concern, various forms of academic support are offered by higher education institutions to nurture and develop the pipeline of postgraduate students. The support provided to postgraduate students tends to emphasize academic support at times at the expense of psychosocial or non-academic support. Non-cognitive skills were underscored as integral to determining academic and employment outcomes and thus, may need to be investigated more. This manuscript reports on an attempt to filter and consolidate the literature reporting on interventions for postgraduate students that include the development of non-cognitive skills. A systematic review was conducted, because it enabled rigorous and replicable process of consolidating literature. Covidence software was used as a digital platform for the systematic review. The review was conducted at four levels as per the PRISMA guideline namely, identification, screening, eligibility and final summation. The filtration process attempted to answer the following research questions: (1) How are non-cognitive factors or skills defined? (2) Which non-cognitive skills were included in support for postgraduate (Masters and Doctoral) students in the higher education setting?, and (3) How have non-cognitive skills been included in support interventions provided to retain postgraduate students? Descriptive and theory explicative metasynthesis was used for the summation and data extraction. The primary finding was that the term non-cognitive was not used explicitly in the included studies to describe skills or factors supporting student retention. The discourse centered around support and social support as non-academic factors and skills. This suggested that non-cognitive skills were constructed as co-curricular and not integrated into the postgraduate academic project or core learning outcomes. The findings highlighted the distinction between non-cognitive skills and factors and illustrated how skills and factors operate at different levels with different spheres of influence. The formats of support provide an intersectional space where skills and factors are combined.